The Role of the Green Economy in Economic Growth in Indonesia Based on an Islamic Economic Perspective - Yulitasari, Lis; Suryanto, Tulus; Syamsul Hilal, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Over the past few years, the concept of a green economy has been recognized as a vital mechanism for achieving economic progress in both developed and emerging nations. This study aims to analyze the role of the green economy in Indonesia's economic expansion based on an Islamic economic perspective. The research methodology employs library analysis and content assessment. The data sources utilized in this study were gathered from previous research, articles, regulations, and reference literature pertaining to green economics, economic growth, and Islamic economics. The results denote that the green economy bears tremendous potential to support economic advancement in Indonesia under an Islamic economic lens. By applying key tenets such as the obligation to safeguard nature and the judicious utilization of resources, Indonesia can cultivate a development paradigm that is sustainable and beneficial across all societal strata. This research recommends that private and public sector entities continue endorsing and integrating green economy principles moving forward. Specifically, Islamic financial instruments can be directed toward eco-friendly investments like renewable energy, sustainable agriculture, green technologies, and environmentally-conscious infrastructure. Such participations from Islamic economics in "greening" the economy signify promising trajectories aligning ethical and sustainable finance. As the world grapples with urgent ecological crises, policy frameworks in Indonesia should incentivize collective societal and commercial transitions toward greener fiscal practices. Islamic finance with its underlying moral philosophy can potentially transform finance itself into an apparatus upholding both economic and environmental welfare.